The damage response of RC columns with considering different longitudinal and shear reinforcement under demolition blasting. (15th December 2022) - Yan, Yu; Hou, Xiaomeng; Zheng, Wenzhong; Fei, Honglu
Abstract: To investigate the effects of longitudinal and shear reinforcement on the stability and damage response (i.e., the size of damaged zone, bending deflection of longitudinal reinforcement and exposed length of longitudinal reinforcement) of reinforced concrete columns during blasting demolition of structure, a series of tests were conducted considering different longitudinal reinforcement diameters, shear reinforcement diameters and shear reinforcement spacings. The blast failure process was conducted to investigate the mechanism of the formation of damaged zones in RC columns. Based on the test results, it was concluded that shear reinforcement took a more significant role in the damage response of the column than longitudinal reinforcement. Meanwhile, the relationships between the damage response and the diameter of longitudinal and shear reinforcement were established based on dimensional analysis, respectively. Furthermore, this study developed a more accurate prediction model of damage response to optimize the blasting design parameters and improve the economy and safety of demolition blasting. Finally, an effective energy concept was introduced to evaluate the utilization rate of explosive energy. Highlights: The effects of longitudinal and shear reinforcement on the damage effects of RC columns were investigated by tests. The size of concrete fragment was screened by image. The prediction models of the damaged effects of RC columns were developed. The effective energy concept was first introduced to evaluate the utilization rate of explosive energy.